Exploring determinants of time to school re-entry after pediatric epilepsy surgery - Evangeline A. Huis in 't Veld; Olga Braams; Willem M. Otte; Peter van Rijen; Kees P.J. Braun; Renske Schappin (Epilepsy & Behavior Reports)
After epilepsy surgery, it varies when children re-enter school. The aim of this study was to identify determinants for this variation. Parents of 21 school-attending children participated in semi-structured interviews during their child’s hospitalization for epilepsy surgery and one year afterward (based on the standard neuropsychological post-surgical follow-up). The mean time to school re-entry was 10.7 weeks (SD = 6.3). One child did not attend school after one year, whilst the fastest child resumed school 2 weeks after surgery. We performed univariable linear regression models with bootstrapped R2 for all variables deemed theoretically or clinically relevant to school re-entry. We found that temporal surgery was significantly related to shorter time to school re-entry; and that longer hospitalization, and presurgical outpatient educational counseling were significantly related to longer time to school re-entry. In multivariable linear regression, these variables together predicted 57% of variance (bootstrapped) in time to school re-entry. In conclusion, our findings indicate that school re-entry varies considerably among children but can partly be explained by surgery related variables and the presence of counseling. Given the importance of school in children’s daily lives, we argue that school attendance should be stimulated by increasing professionals’ awareness of children’s school re-entry process.